Nanoprodrugs of NSAIDs Inhibit the Growth of U87-MG Glioma Cells. (17th March 2010) - Lee, Bong-Seop; Yuan, Xiangpeng; Xu, Qijin; Ko, Minhee K.; Nalla, Aruna K.; Frankiel, Ilana; Shear, Talia; Black, Keith L.; Yu, John S.
Abstract : Several recent reports have demonstrated that nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit the growth of various malignant cells suggesting their application as anticancer agents. In this study, we prepared six nanometer-sized prodrugs (nanoprodrugs) of NSAIDs, ibuprofen, indomethacin, and naproxen through the spontaneous emulsification mechanism using monomeric and dimeric derivatives of the NSAIDs. We evaluated their effect on the proliferation of U87-MG glioma cells by cell counting, WST-1 cell proliferation reagent, and propidium iodide incorporation. The two ibuprofen nanoprodrugs inhibited the cell growth more potently than the indomethacin nanoprodrugs, whereas the naproxen nanoprodrugs did not show any significant effect. Remarkably, ibuprofen did not show any effect at an equimolar concentration. Approximately, 4.4% of the ibuprofen nanoprodrugs was found in the cell, whereas no ibuprofen could be detected suggesting that the superior effect of the nanoprodrugs can be attributed to the efficient cellular uptake of the nanoprodrugs.